Bio-based furandicarboxylic acid copolyester and preparation method thereof
The method improves the crystallization and mechanical properties of bio-based furandicarboxylic acid copolyesters by esterification and polycondensation, forming a block copolyester with controlled hard and soft segments, enhancing thermal stability and applicability in textiles and medicine.
Patent Information
- Application Number
- CN202411370200.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-20
AI Technical Summary
Existing bio-based polymers derived from 2,5-furandicarboxylic acid suffer from poor crystallization performance, which affects their mechanical properties and heat resistance, limiting their application in fields like medicine and textiles.
A method involving esterification and polycondensation reactions under negative pressure, using 2,5-furandicarboxylic acid, bio-based diols (such as ethylene glycol, propylene glycol, butanediol), sorbitol, and macromolecular polyethers, with specific catalysts and stabilizers, to form a furandicarboxylic acid block copolyester with controlled hard and soft segments, enhancing crystallinity and thermal stability.
The resulting copolyester exhibits improved mechanical strength, heat resistance, hydrophilicity, and degradability, with controlled crystallinity, suitable for textile and medical applications.
Smart Images

Figure CN119161565A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bio-based polymer materials, and in particular to a bio-based furandicarboxylic acid copolyester and a preparation method thereof. Background Art
[0002] Bio-based polymers are polymers obtained by converting bio-based resources as raw materials. As a renewable resource, they have good application prospects in the fields of medicine, textiles, etc. Currently, commonly used bio-based polymer materials include polylactic acid (PLA), polyhydroxy fatty acids (PHA), polyglycolic acid (PGA), polybutylene glycol succinate (PBS), etc., but these fat polymers have poor mechanical properties and heat resistance, which seriously limits their application scope.
[0003] The prior art proposes to prepare bio-based polymers using 2,5-furandicarboxylic acid as a raw material to improve the mechanical properties and heat resistance of the material. For example, patent document CN118221920A discloses a furandicarboxylic acid block copolyester, which is obtained by copolymerizing 2,5-furandicarboxylic acid with two diols, namely, bio-based diol and isosorbide, and polyethylene glycol. The material has good heat resistance and mechanical properties.
[0004] However, due to the geometric structure and rigidity of 2,5-furandicarboxylic acid, the crystallization performance of furan-based polyester is poor. If a large cyclic steric group is introduced to copolymerize it, the crystallization of the copolyester will be further hindered or even impossible to crystallize. In the medical and textile fields, the crystallization ability of the fiber-forming polymer and its own crystallinity largely affect the physical and mechanical properties of the fiber. In addition, the crystallization process helps to fix the orientation state during the transition from amorphous to crystalline state, which can directly determine the post-processing performance of the fiber and the properties of the finished fiber. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to improve the crystallization performance of bio-based furandicarboxylic acid copolyester and develop a fiber-forming polymer with a certain degree of crystallinity.
[0006] In order to achieve the above object, the present invention provides a method for preparing bio-based furandicarboxylic acid copolyester, comprising the following steps:
[0007] S1. Add 2,5-furandicarboxylic acid, bio-based diol, sorbitol and an esterification catalyst in a molar ratio of 1:(1.2-2.0):(0.001-0.01):(0.0005-0.005) into a reaction container, and carry out an esterification reaction under a negative pressure of a nitrogen atmosphere to obtain an oligomer;
[0008] S2, adding a macromolecular polyether and a polycondensation catalyst to a reaction container, wherein the molar ratio of 2,5-furandicarboxylic acid, the macromolecular polyether and the polycondensation catalyst is 1:(0.03-0.3):(0.0005-0.005), increasing the vacuum degree of the reaction container, and performing a prepolymerization reaction to obtain a prepolymer;
[0009] S3, increasing the vacuum degree of the reaction container again to carry out polycondensation reaction to obtain bio-based furandicarboxylic acid copolyester.
[0010] The present invention uses 2,5-furandicarboxylic acid and two diols, namely, bio-based diol and sorbitol, and polyether as raw materials, adopts negative pressure esterification-melt polycondensation, and copolymerizes to obtain furandicarboxylic acid block copolyester with a certain crystallinity by regulating the molar amount of sorbitol and polyether. The material has broad application prospects in the fields of textile and medical treatment.
[0011] Furthermore, the bio-based diol is selected from one of bio-based ethylene glycol, bio-based propylene glycol, and bio-based butanediol. In the present invention, furan dibasic acid is first subjected to esterification reaction with bio-based diol and bio-based polyol. The polyhydroxy structure of sorbitol can effectively improve the hydrophilicity and degradability of the copolyester, and also causes the molecular chain to form branches and even slightly cross-links, which together with the rigid furan ring structure give the copolyester excellent mechanical strength and heat resistance. Excessive bio-based diol ensures the esterification rate, and the unreacted bio-based diol can be slowly removed from the system under low vacuum conditions through pre-polycondensation reaction due to its low boiling point.
[0012] Further, the esterification catalyst is selected from at least one of anhydrous zinc acetate, anhydrous cobalt acetate, stannous oxalate, dibutyltin oxide, dibutyltin dilaurate, tetrabutyl titanate, antimony acetate and antimony trioxide;
[0013] And / or, the polycondensation catalyst is at least one selected from antimony-based catalysts, germanium-based catalysts, and tin-based catalysts.
[0014] Furthermore, the macromolecular polyether is selected from one of polyethylene glycol, polypropylene glycol and polytetrahydrofuran diol, and the molar mass of the macromolecular polyether is 600 to 6000 g / mol. The invention adds the macromolecular polyether in the prepolymerization reaction to prevent the thermal degradation of the polyether due to long-term esterification, and avoids the influence of the molecular weight reduction of the polyether on the control design of the soft and hard segment ratio of the copolyester.
[0015] Furthermore, in step S2, a stabilizer and an antioxidant are added to the reaction system, and the molar ratio of 2,5-furandicarboxylic acid, the stabilizer and the antioxidant is 1:(0.0005-0.005):(0.001-0.005). Adding a heat stabilizer and an antioxidant in the prepolymerization stage can effectively avoid the discoloration problem caused by thermal degradation and thermal oxidation side reactions of the furan-based polyester under continuous high temperature conditions, thereby obtaining a light-colored or even colorless furan-based copolyester.
[0016] Further, the stabilizer is selected from at least one of phosphoric acid, phosphorous acid, triethyl phosphate, triphenyl phosphate and triphenyl phosphite;
[0017] And / or, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1098, antioxidant 1222, and antioxidant 168.
[0018] Furthermore, in step S1, the conditions of the esterification reaction are as follows: the reaction temperature is 170-190° C., the reaction pressure is 50-90 KPa, and the reaction time is 3-5 h.
[0019] Furthermore, in step S2, the conditions for the prepolymerization reaction are as follows: the reaction temperature is 190-210° C., the reaction pressure is 40 KPa-1 KPa, and the reaction time is 0.5-1.5 h.
[0020] Furthermore, in step S3, the conditions of the polycondensation reaction are as follows: the reaction temperature is 210-230° C., the reaction pressure is less than 30 Pa, and the reaction time is 1-5 h.
[0021] The present invention performs esterification reaction under negative pressure conditions, which is conducive to the distillation of byproduct water, accelerates the esterification rate, controls the esterification temperature within 190°C, and can effectively reduce the side reactions such as decarboxylation of 2,5-furandicarboxylic acid while ensuring the esterification rate, and inhibits the yellowing of the product. Macromolecular polyether is added to the prepolymerization reaction, and a block copolymer with flexible aliphatic polyether macromolecules as soft segments and rigid bio-based aromatic polyesters as hard segments is formed through polycondensation. The hard segments and soft segments are connected by covalent bonds. The hard segments crystallized at room temperature will limit the activity of the soft segments to form physical crosslinking points, so that the copolyester has both excellent mechanical strength and thermal properties and good elasticity.
[0022] The present invention also provides a bio-based furandicarboxylic acid copolyester prepared by the above preparation method, and its structural formula is:
[0023]
[0024] Wherein, R1 is selected from one of the structural units of ethylene glycol, propylene glycol, and butylene glycol, R2 is selected from one of the structural units of polyethylene glycol, polypropylene glycol, and polytetrahydrofuran diol, and x, y, and z are all integers of 1 to 80.
[0025] The present invention uses flexible aliphatic polyether macromolecules as soft segments and rigid bio-based aromatic polyesters as hard segments. The mass ratio of the hard segment to the soft segment is controlled within a reasonable range, thereby obtaining a crystallizable light-colored furandicarboxylic acid block copolyester. The material has high glass transition temperature and thermal decomposition temperature, and has good mechanical properties, hydrophilicity, degradability and biocompatibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the 1H-NMR spectrum of the bio-based furandicarboxylic acid copolyester prepared in Example 1 of the present invention.
[0027] Figure 2 This is the DSC spectrum of the bio-based furandicarboxylic acid copolyester prepared in Example 1 of the present invention.
[0028] Figure 3 This is a slice sample picture of the bio-based furandicarboxylic acid copolyester prepared in Example 1 of the present invention.
[0029] Figure 4 This is the 1H-NMR spectrum of the bio-based furandicarboxylic acid copolyester prepared in Example 2 of the present invention.
[0030] Figure 5 This is the DSC spectrum of the bio-based furandicarboxylic acid copolyester prepared in Example 2 of the present invention.
[0031] Figure 6 This is a slice sample picture of the bio-based furandicarboxylic acid copolyester prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention without departing from the scope or spirit of the present invention. Other embodiments obtained from the present invention description will be apparent to those skilled in the art.
[0035] The specific embodiment of the present invention provides a bio-based furandicarboxylic acid copolyester, the structural formula of which is:
[0036]
[0037] Among them, R1 is selected from one of the structural units of ethylene glycol, propylene glycol, and butylene glycol, R2 is selected from one of the structural units of polyethylene glycol, polypropylene glycol, and polytetrahydrofuran diol, x, y, and z are all integers of 1 to 80, and (x+y):z=(5 to 50):1. The block copolymer uses a flexible aliphatic polyether macromolecule as a soft segment and a rigid bio-based aromatic polyester as a hard segment. The mass ratio of the hard segment to the soft segment is controlled within the range of (30 to 60):50, the crystallinity is between 5% and 32%, the fiber-forming polymer has a high glass transition temperature and a thermal decomposition temperature, and has good mechanical properties, hydrophilicity, degradability, and biocompatibility, and has broad application prospects in the textile and medical fields.
[0038] The specific steps of the preparation method of the bio-based furandicarboxylic acid copolyester are as follows:
[0039] S1. Add 2,5-furandicarboxylic acid, bio-based diol, sorbitol and an esterification catalyst into a reaction container, and carry out an esterification reaction under a negative pressure of a nitrogen atmosphere to obtain an oligomer.
[0040] In a specific embodiment, the bio-based diol can be selected from bio-based ethylene glycol, bio-based propylene glycol, bio-based butylene glycol, etc.; the esterification catalyst can be selected from anhydrous zinc acetate, anhydrous cobalt acetate, stannous oxalate, dibutyltin oxide, dibutyltin dilaurate, tetrabutyl titanate, antimony acetate and antimony trioxide. The molar ratio of each raw material is controlled, specifically, 2,5-furandicarboxylic acid: bio-based diol: sorbitol: esterification catalyst = 1: (1.2-2.0): (0.001-0.01): (0.0005-0.005).
[0041] In this step, furan dicarboxylic acid is subjected to esterification reaction with bio-based diols and bio-based polyols. The polyhydroxy structure of the bio-based polyols can effectively improve the hydrophilicity and degradability of the copolyester, and also cause the molecular chain to form branches and even slightly cross-link. Together with the rigid furan ring structure, it gives the copolyester excellent mechanical strength and heat resistance. The excess bio-based diols ensure the esterification rate.
[0042] In a specific embodiment, the conditions of the esterification reaction are as follows: the reaction temperature is 170-190°C, the reaction pressure is 50-90KPa, and the reaction time is 3-5h. In this step, the esterification reaction is carried out under negative pressure conditions, which is conducive to the distillation of the by-product water, accelerates the esterification rate, controls the esterification temperature within 190°C, and effectively reduces the side reactions such as the decarboxylation of 2,5-furandicarboxylic acid and the etherification of ethylene glycol while ensuring the esterification rate, inhibits the yellowing of the product, and also improves the regularity of the hard segment to a certain extent.
[0043] S2, add macromolecular polyether, polycondensation catalyst stabilizer and antioxidant to the reaction container, increase the vacuum degree of the reaction container, perform prepolymerization, and obtain a prepolymer. In a specific embodiment, the conditions of the prepolymerization reaction are as follows: the reaction temperature is 190-210°C, the reaction pressure is 40KPa-1KPa, and the reaction time is 0.5-1.5h. Adding macromolecular polyether to the prepolymerization reaction can prevent the thermal degradation of the polyether due to long-term esterification, and avoid the influence of the molecular weight reduction of the polyether on the control design of the soft and hard segment ratio of the copolyester.
[0044] In a specific embodiment, the macromolecular polyether may be polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc., and the molar mass of the macromolecular polyether is 600-6000 g / mol; the condensation catalyst may be an antimony-based catalyst, a germanium-based catalyst, a tin-based catalyst, etc.; the stabilizer may be phosphoric acid, phosphorous acid, triethyl phosphate, triphenyl phosphate, and triphenyl phosphite, etc.; the antioxidant may be antioxidant 1010, antioxidant 1098, antioxidant 1222, antioxidant 168, etc.
[0045] The amount of raw materials added in this step is regulated according to the amount of 2,5-furandicarboxylic acid used, and the molar ratio of each raw material is as follows: 2,5-furandicarboxylic acid: macromolecular polyether: polycondensation catalyst: stabilizer: antioxidant = 1: (0.03-0.3): (0.0005-0.005): (0.0005-0.005): (0.001-0.005).
[0046] S3, increasing the vacuum degree of the reaction container again, performing polycondensation reaction, and obtaining bio-based furandicarboxylic acid copolyester. In a specific embodiment, the conditions of the polycondensation reaction are as follows: reaction temperature is 210-230° C., reaction pressure is less than 30 Pa, and reaction time is 1-5 h.
[0047] In this step, a block copolymer with a flexible aliphatic polyether macromolecule as a soft segment and a rigid bio-based aromatic polyester as a hard segment is formed through a condensation reaction. The hard segment and the soft segment are connected by covalent bonds. The hard segment crystallized at room temperature will limit the mobility of the soft segment to form physical cross-linking points, so that the copolyester has both excellent mechanical strength and thermal properties and good elasticity.
[0048] The technical solutions and effects of the present invention are illustrated below in conjunction with specific embodiments.
[0049] In the embodiment of the present invention, the nuclear magnetic resonance hydrogen spectrum ( 1 H-NMR was performed using an AVANCE NEO 400 MHz nuclear magnetic resonance spectrometer from BRUKER, Switzerland, with deuterated trifluoroacetic acid (CF3COOD) as solvent and tetramethylsilane (TMS) as internal standard.
[0050] The intrinsic viscosity was measured in accordance with GB / T 14190-2008 “Test method for fiber-grade polyester chips (PET)” using phenol / tetrachloroethane (m:m=1:1) as solvent at 25±0.05°C using an Ubbelohde viscometer. The experimental results were calculated using formulas (1)-(3).
[0051]
[0052] Where: η r is the relative viscosity; η sp is the specific viscosity; [η] is the intrinsic viscosity, dL / g; t1 and t0 are the outflow times of the polymer solution and the pure solvent, s; c is the concentration of the polymer solution, g / dL.
[0053] The chromaticity (Lab value) refers to the dry crushing method of the chromaticity test in GB / T 14190-2008 "Test method for fiber-grade polyester chips (PET)", and is measured using a Minolta CM-26d integrating sphere colorimeter.
[0054] Differential scanning calorimetry (DSC) was performed using a DSC214 differential scanning calorimeter from NETZSCH, Germany. The test temperature range was 25°C to 250°C under a N2 atmosphere, and the heating rate was 10°C / min. The samples were vacuum dried at 120°C for 6 h before testing.
[0055] The water contact angle test was performed using an OCA20 contact angle measuring instrument from Dataphysics of Germany at 20°C and 65%. Before the test, the sample was vacuum dried at 110°C for 12 hours and melt-molded at 200-225°C to obtain a long strip.
[0056] Example 1
[0057] In this example, bio-based furandicarboxylic acid copolyesters were prepared by the following method:
[0058] (1) 2,5-Furandicarboxylic acid, bio-based ethylene glycol, sorbitol and anhydrous zinc acetate were added into a polymerization kettle preheated to 80°C in a molar ratio of 1:1.8:0.003:0.001, and stirred and mixed. After vacuuming and replacing nitrogen three times, the temperature was gradually raised to 185°C. The initial pressure of the reaction system was 70 KPa. The pressure in the system continued to rise as the esterification proceeded and then remained stable. The esterification reaction was carried out for 5.5 hours to obtain an oligomer.
[0059] (2) Add 5% of polyethylene glycol (600 g / mol) based on the molar amount of 2,5-furandicarboxylic acid, 0.05% of antimony trioxide, 0.1% of antioxidant 1010 and 0.1% of triphenyl phosphate into a polymerization kettle, raise the temperature to 205° C., slowly evacuate to maintain the pressure at 4000 Pa, and perform prepolymerization for 45 minutes to obtain a prepolymer.
[0060] (3) The polymerization kettle was gradually heated to 230° C. and vacuumed to 20 Pa. The reaction was continued for 4 h to obtain bio-based furandicarboxylic acid copolyester.
[0061] The samples of copolymers prepared in this example are as follows Figure 3 As shown, its H NMR spectrum 1 H-NMR Figure 1 As shown, the characteristic peak at 7.290ppm is attributed to the hydrogen atoms on the furan ring; the characteristic peak at 4.709ppm is attributed to the hydrogen atoms of the methylene in the PEF segment; the characteristic peak at 4.2-5.8ppm is caused by -CH2 or CH in various chemical environments on the sorbitol in the chain; the characteristic peaks at 4.602ppm, 4.086ppm, and 3.940ppm belong to the chemical shifts of the methylene in three different chemical environments in the soft segment PEGF segment, indicating that the product is a multi-block copolymer, and the polymer backbone consists of polyethylene glycol as the soft segment and poly(ethylene furandicarboxylate-co-sorbitol furandicarboxylate) as the hard segment.
[0062] After testing, the intrinsic viscosity of the bio-based furandicarboxylic acid copolyester prepared in this embodiment is 0.82 dL / g, the Lab value is 6.2; the glass transition temperature is 89°C, and the melting point is 212.0°C (DSC curve is as shown in Figure 2 The crystallinity is 25.3%, the tensile strength is 82 MPa, the elongation at break is 36%, and the water surface contact angle is 82.4°.
[0063] Example 2
[0064] In this example, bio-based furandicarboxylic acid copolyesters were prepared by the following method:
[0065] (1) 2,5-Furandicarboxylic acid, bio-based propylene glycol, sorbitol and anhydrous zinc acetate were added into a polymerization kettle preheated to 80°C in a molar ratio of 1:1.6:0.002:0.001, and stirred and mixed. After evacuation and nitrogen replacement three times, the temperature was gradually raised to 190°C. The initial pressure of the reaction system was 50 KPa. The pressure in the system continued to rise as the esterification proceeded and then remained stable. The esterification reaction lasted for 3.5 hours to obtain an oligomer.
[0066] (2) Add 5% of polypropylene glycol (1000 g / mol) based on the molar amount of 2,5-furandicarboxylic acid, 0.05% of antimony trioxide, 0.1% of antioxidant 1010 and 0.1% of triphenyl phosphate into a polymerization kettle, raise the temperature to 210° C., slowly evacuate to maintain the pressure at 1000 Pa, and perform prepolymerization for 30 minutes to obtain a prepolymer.
[0067] (3) The polymerization kettle was gradually heated to 230° C., and the vacuum was continued to be evacuated to 10 Pa. The reaction was continued for 5 h to obtain bio-based furandicarboxylic acid copolyester.
[0068] The samples of copolymers prepared in this example are as follows Figure 6 As shown, its H NMR spectrum 1 H-NMR Figure 4 As shown, the characteristic peaks at 7.170ppm and 7.153ppm are attributed to the hydrogen atoms on the furan ring; the characteristic peaks at 4.451ppm and 2.178ppm are attributed to the hydrogen atoms of the methylene in the PTF segment; the characteristic peaks at 4.369ppm, 3.720ppm, 3.604ppm, 2.133ppm, and 2.082ppm are the chemical shifts of the methylene in the soft segment PPGF segment under five different chemical environments; the characteristic peak of 4.2-5.8ppm is caused by -CH2 or CH on the sorbitol in the chain in various chemical environments, indicating that the product is a multi-block copolymer, and the polymer backbone is composed of polypropylene glycol as the soft segment and poly(propylene furandicarboxylate-co-sorbitol furandicarboxylate) as the hard segment.
[0069] After testing, the intrinsic viscosity of the bio-based furandicarboxylic acid copolyester prepared in this embodiment is 0.78 dL / g, the Lab value is 8.7; the glass transition temperature is 55.2°C, and the melting point is 162°C (DSC curve is as shown in Figure 5 The crystallinity is 14% and the water surface contact angle is 85.7°.
[0070] Example 3
[0071] In this example, bio-based furandicarboxylic acid copolyesters were prepared by the following method:
[0072] (1) 2,5-Furandicarboxylic acid, bio-based butanediol, sorbitol and anhydrous cobalt acetate were added into a polymerization kettle preheated to 80°C in a molar ratio of 1:1.8:0.005:0.0015, and stirred and mixed. After vacuuming and replacing nitrogen three times, the temperature was gradually raised to 190°C. The initial pressure of the reaction system was 90 KPa. The pressure in the system continued to rise as the esterification proceeded and then remained stable. The esterification reaction was carried out for 4 hours to obtain oligomers.
[0073] (2) Add polyethylene glycol (1000 g / mol) of 10% of the molar amount of 2,5-furandicarboxylic acid, 0.08% of stannous octoate, 0.10% of antioxidant 1098 and 0.2% of triethyl phosphate into a polymerization kettle, raise the temperature to 200° C., slowly evacuate to maintain the pressure at 6000 Pa, and perform prepolymerization for 60 minutes to obtain a prepolymer.
[0074] (3) The polymerization kettle was gradually heated to 220° C., and the vacuum was continued to be evacuated to 10 Pa. The reaction was continued for 4 hours to obtain bio-based furandicarboxylic acid copolyester.
[0075] After testing, the bio-based furandicarboxylic acid copolyester prepared in this example has an intrinsic viscosity of 1.30 dL / g, a Lab value of 11.2, a glass transition temperature of 32° C., a melting point of 159.8° C., a crystallinity of 26.5%, and a water surface contact angle of 70.2°.
[0076] Example 4
[0077] In this example, bio-based furandicarboxylic acid copolyesters were prepared by the following method:
[0078] (1) 2,5-Furandicarboxylic acid, bio-based ethylene glycol, sorbitol and tetrabutyl titanate were added into a polymerization kettle preheated to 80°C in a molar ratio of 1:2.0:0.006:0.001, and stirred and mixed. After evacuation and nitrogen replacement three times, the temperature was gradually raised to 185°C. The initial pressure of the reaction system was 85 KPa. The pressure in the system continued to rise as the esterification proceeded and then remained stable. The esterification reaction was carried out for 3 hours to obtain oligomers.
[0079] (2) Add polyethylene glycol (2000 g / mol) with a molar amount of 10% of 2,5-furandicarboxylic acid, 0.1% of germanium oxide, 0.1% of antioxidant 168 and 0.1% of triphenyl phosphite to a polymerization kettle, raise the temperature to 195° C., slowly evacuate to maintain the pressure at 5000 Pa, and perform prepolymerization for 90 minutes to obtain a prepolymer.
[0080] (3) The polymerization kettle was gradually heated to 225° C., and the vacuum was continued to be evacuated to 20 Pa. The reaction was continued for 3 h to obtain bio-based furandicarboxylic acid copolyester.
[0081] After testing, the bio-based furandicarboxylic acid copolyester prepared in this example has an intrinsic viscosity of 0.96 dL / g, a Lab value of 10.8, a glass transition temperature of 70° C., a melting point of 180.2° C., a crystallinity of 10.2%, and a water surface contact angle of 69.7°.
[0082] Example 5
[0083] In this example, bio-based furandicarboxylic acid copolyesters were prepared by the following method:
[0084] (1) 2,5-Furandicarboxylic acid, bio-based ethylene glycol, sorbitol and dibutyltin dilaurate were added into a polymerization kettle preheated to 80°C in a molar ratio of 1:1.5:0.005:0.002, and stirred and mixed. After evacuation and nitrogen replacement three times, the temperature was gradually raised to 170°C. The initial pressure of the reaction system was 70 KPa. The pressure in the system continued to rise as the esterification proceeded and then remained stable. The esterification reaction was carried out for 4 hours to obtain oligomers.
[0085] (2) Add 10% of polytetrahydrofuran diol (1000 g / mol) of 2,5-furandicarboxylic acid molar amount, 0.1% of antimony trioxide, 0.15% of antioxidant 1222 and 0.05% of triethyl phosphate into a polymerization kettle, raise the temperature to 205° C., slowly evacuate to maintain the pressure at 3000 Pa, and perform prepolymerization for 60 min to obtain a prepolymer.
[0086] (3) The polymerization kettle was gradually heated to 225° C., and the vacuum was continued to be evacuated to 30 Pa. The reaction was continued for 3.5 hours to obtain bio-based furandicarboxylic acid copolyester.
[0087] After testing, the bio-based furandicarboxylic acid copolyester prepared in this example has an intrinsic viscosity of 1.04 dL / g, a Lab value of 11.5, a glass transition temperature of 69° C., a melting point of 178.4° C., a crystallinity of 12.6%, and a water surface contact angle of 76.8°.
[0088] Example 6
[0089] In this example, bio-based furandicarboxylic acid copolyesters were prepared by the following method:
[0090] (1) 2,5-Furandicarboxylic acid, bio-based ethylene glycol, sorbitol and anhydrous zinc acetate were added into a polymerization kettle preheated to 80°C in a molar ratio of 1:1.2:0.0001:0.001, and stirred and mixed. After vacuuming and replacing nitrogen three times, the temperature was gradually raised to 190°C. The initial pressure of the reaction system was 50 KPa. The pressure in the system continued to rise as the esterification proceeded and then remained stable. The esterification reaction was carried out for 5 hours to obtain an oligomer.
[0091] (2) Add 3% of polyethylene glycol (6000 g / mol) based on the molar amount of 2,5-furandicarboxylic acid, 0.05% of antimony trioxide, 0.1% of antioxidant 1010 and 0.1% of triphenyl phosphite into a polymerization kettle, raise the temperature to 210° C., slowly evacuate to maintain the pressure at 5000 Pa, and perform prepolymerization for 30 minutes to obtain a prepolymer.
[0092] (3) The polymerization kettle was gradually heated to 230° C. and vacuumed to 20 Pa. The reaction was continued for 4 h to obtain bio-based furandicarboxylic acid copolyester.
[0093] After testing, the bio-based furandicarboxylic acid copolyester prepared in this example has an intrinsic viscosity of 0.62 dL / g, a Lab value of 8.6, a glass transition temperature of 92° C., a melting point of 214.5° C., a crystallinity of 30.6%, and a water surface contact angle of 65.3°.
[0094] Comparative Example 1
[0095] This comparative example prepares bio-based furandicarboxylic acid copolyester by the following method:
[0096] (1) 2,5-Furandicarboxylic acid, bio-based ethylene glycol, sorbitol and anhydrous zinc acetate were added into a polymerization kettle preheated to 80°C in a molar ratio of 1:1.8:0.2:0.001, and stirred and mixed. After evacuation and nitrogen replacement three times, the temperature was gradually raised to 185°C. The initial pressure of the reaction system was 70 KPa. The pressure in the system continued to rise as the esterification proceeded and then remained stable. The esterification reaction was carried out for 5.5 hours to obtain an oligomer.
[0097] (2) Add 5% of polyethylene glycol (600 g / mol) based on the molar amount of 2,5-furandicarboxylic acid, 0.05% of antimony trioxide, 0.1% of antioxidant 1010 and 0.1% of triphenyl phosphate into a polymerization kettle, raise the temperature to 205° C., slowly evacuate to maintain the pressure at 4000 Pa, and perform prepolymerization for 45 minutes to obtain a prepolymer.
[0098] (3) The polymerization kettle was gradually heated to 230° C., and the vacuum was continued to be evacuated to 20 Pa. The reaction was continued for 1 hour to obtain bio-based furandicarboxylic acid copolyester.
[0099] Since the amount of sorbitol added in this comparative example is too much, obvious cross-linking occurs after 0.5 h of the polycondensation reaction, the molecular chains are excessively entangled, the solubility is extremely poor, and relevant data such as the intrinsic viscosity cannot be characterized.
[0100] Comparative Example 2
[0101] This comparative example prepares bio-based furandicarboxylic acid copolyester by the following method:
[0102] (1) 2,5-Furandicarboxylic acid, bio-based ethylene glycol, sorbitol and anhydrous zinc acetate were added into a polymerization kettle preheated to 80°C in a molar ratio of 1:1.6:0.002:0.001, and stirred and mixed. After vacuuming and replacing nitrogen three times, the temperature was gradually raised to 190°C. The initial pressure of the reaction system was 60 KPa. The pressure in the system continued to rise as the esterification proceeded and then remained stable. The esterification reaction was carried out for 5 hours to obtain an oligomer.
[0103] (2) Add 30% of the molar amount of 2,5-furandicarboxylic acid polytetrahydrofuran diol (1000 g / mol), 0.05% of antimony trioxide, 0.1% of antioxidant 1010 and 0.1% of triphenyl phosphate into a polymerization kettle, raise the temperature to 210° C., slowly evacuate to maintain the pressure at 1000 Pa, and perform prepolymerization for 30 min to obtain a prepolymer.
[0104] (3) The polymerization kettle was gradually heated to 230° C. and vacuumed to 10 Pa. The reaction was continued for 4 h to obtain bio-based furandicarboxylic acid copolyester.
[0105] After testing, the intrinsic viscosity of the bio-based furandicarboxylic acid copolyester prepared in this example is 1.35 dL / g, the Lab value is 12.6, the sample cannot be crystallized and is in an amorphous state, and the water surface contact angle is 60.2°.
[0106] Comparative Example 3
[0107] This comparative example prepares bio-based furandicarboxylic acid copolyester by the following method:
[0108] (1) 2,5-Furandicarboxylic acid, bio-based ethylene glycol, isosorbide and anhydrous zinc acetate were added into a polymerization kettle preheated to 80° C. in a molar ratio of 1:2:0.1:0.0015, and stirred and mixed. After nitrogen was replaced three times, the temperature was gradually raised to 185° C., and an esterification reaction was carried out at normal pressure for 5.5 hours to obtain an oligomer.
[0109] (2) Add polyethylene glycol (2000 g / mol) with a molar amount of 10% of 2,5-furandicarboxylic acid, 0.05% of antimony trioxide, 0.1% of antioxidant 1010 and 0.1% of triphenyl phosphate into a polymerization kettle, raise the temperature to 205° C., slowly evacuate to maintain the pressure at 4000 Pa, and carry out prepolymerization for 45 minutes to obtain a prepolymer.
[0110] (3) The polymerization kettle was gradually heated to 230° C. and vacuumed to 20 Pa. The reaction was continued for 4.5 h to obtain bio-based furandicarboxylic acid copolyester.
[0111] After testing, the intrinsic viscosity of the bio-based furandicarboxylic acid copolyester prepared in this example is 1.15 dL / g, the Lab value is 18.2, the glass transition temperature is 84° C., the sample cannot crystallize and is in an amorphous state, and the water surface contact angle is 86.9°.
[0112] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing bio-based furandicarboxylic acid copolyester, characterized in that: The following steps are involved: S1. Add 2,5-furandicarboxylic acid, bio-based diol, sorbitol and an esterification catalyst in a molar ratio of 1:(1.2-2.0):(0.001-0.01):(0.0005-0.005) into a reaction container, and carry out an esterification reaction under a negative pressure of a nitrogen atmosphere to obtain an oligomer; S2, adding a macromolecular polyether and a polycondensation catalyst to a reaction container, wherein the molar ratio of 2,5-furandicarboxylic acid, the macromolecular polyether and the polycondensation catalyst is 1:(0.03-0.3):(0.0005-0.005), increasing the vacuum degree of the reaction container, and performing a prepolymerization reaction to obtain a prepolymer; S3, increasing the vacuum degree of the reaction container again to carry out polycondensation reaction to obtain bio-based furandicarboxylic acid copolyester.
2. The method for preparing bio-based furandicarboxylic acid copolyester according to claim 1, characterized in that: The bio-based diol is selected from one of bio-based ethylene glycol, bio-based propylene glycol and bio-based butylene glycol.
3. The method for preparing bio-based furandicarboxylic acid copolyester according to claim 1, characterized in that: The esterification catalyst is selected from at least one of anhydrous zinc acetate, anhydrous cobalt acetate, stannous oxalate, dibutyltin oxide, dibutyltin dilaurate, tetrabutyl titanate, antimony acetate and antimony trioxide; And / or, the polycondensation catalyst is at least one selected from antimony-based catalysts, germanium-based catalysts, and tin-based catalysts.
4. The method for preparing bio-based furandicarboxylic acid copolyester according to claim 1, characterized in that: The macromolecular polyether is selected from one of polyethylene glycol, polypropylene glycol and polytetrahydrofuran diol, and the molar mass of the macromolecular polyether is 600-6000 g / mol.
5. The method for preparing bio-based furandicarboxylic acid copolyester according to claim 1, characterized in that: In the step S2, a stabilizer and an antioxidant are further added to the reaction system, and the molar ratio of 2,5-furandicarboxylic acid, the stabilizer and the antioxidant is 1:(0.0005-0.005):(0.001-0.005).
6. The method for preparing bio-based furandicarboxylic acid copolyester according to claim 5, characterized in that: The stabilizer is selected from at least one of phosphoric acid, phosphorous acid, triethyl phosphate, triphenyl phosphate and triphenyl phosphite; And / or, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1098, antioxidant 1222, and antioxidant 168.
7. The method for preparing the bio-based furandicarboxylic acid copolyester according to any one of claims 1 to 6, characterized in that: In step S1, the conditions of the esterification reaction are as follows: the reaction temperature is 170-190° C., the reaction pressure is 50-90 KPa, and the reaction time is 3-5 h.
8. The method for preparing the bio-based furandicarboxylic acid copolyester according to any one of claims 1 to 6, characterized in that: In the step S2, the conditions of the prepolymerization reaction are as follows: the reaction temperature is 190-210° C., the reaction pressure is 40 KPa-1 KPa, and the reaction time is 0.5-1.5 h.
9. The method for preparing the bio-based furandicarboxylic acid copolyester according to any one of claims 1 to 6, characterized in that: In step S3, the conditions of the polycondensation reaction are as follows: the reaction temperature is 210-230° C., the reaction pressure is less than 30 Pa, and the reaction time is 1-5 hours.
10. A bio-based furandicarboxylic acid copolyester, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9, the bio-based furandicarboxylic acid copolyester has the structural formula: Wherein, R1 is selected from one of the structural units of ethylene glycol, propylene glycol, and butylene glycol, R2 is selected from one of the structural units of polyethylene glycol, polypropylene glycol, and polytetrahydrofuran diol, and x, y, and z are all integers of 1 to 80.
Citation Information
Patent Citations
Furandicarboxylic acid block copolyester and preparation method thereof
CN118221920A
